Kepentingan Terbaik Anak dalam Sengketa Harta Bersama: Analisis SEMA No. 1 Tahun 2022 dengan Teori Fath al-Żarī‘ah dan Sadd al-Żarī‘ah - Purwanto, Ahmad Edi (ABHATS: Jurnal Islam Ulil Albab, 2025)
This article examines the Circular Letter of the Supreme Court of the Republic of Indonesia (SEMA) No. 1 of 2022, particularly Point C.1.a, which postpones the division of joint marital property in the form of the only residence occupied by the child until the child reaches 21 years of age, becomes independent, or gets married. The study focuses on how the principle of the best interests of the child is implemented in joint property disputes following divorce, analyzed through the theoretical framework of fath al-Żarī‘ah and sadd al-Żarī‘ah. This research employs a normative juridical approach, emphasizing the interpretation and systematization of legal norms contained in SEMA No. 1 of 2022 and their relevance to the concept of maqāṣid al-sharī‘ah. The findings indicate that postponing the division of the only residential property not only guarantees a decent place to live for the child but also prevents potential neglect resulting from divorce. Thus, this Circular Letter reflects the role of the state in ensuring that judicial considerations prioritize the best interests of the child over other individual rights and interests, in line with the objectives of sharī‘ah to realize jalb al-maṣāliḥ and prevent dar’ al-mafāsid. [Tulisan ini mengkaji Surat Edaran Mahkamah Agung (SEMA) No. 1 Tahun 2022, khususnya Butir C.1.a, yang menunda pembagian harta bersama berupa rumah satu-satunya yang ditempati anak hingga ia berusia 21 tahun, mandiri, atau menikah. Fokus penelitian ini adalah bagaimana asas kepentingan terbaik anak diterapkan dalam sengketa harta bersama pasca perceraian, dengan menggunakan pendekatan teori fath al-Żarī‘ah dan sadd al-Żarī‘ah. Penelitian ini bersifat yuridis normatif dengan analisis terhadap norma hukum yang terkandung dalam SEMA No. 1 Tahun 2022 serta relevansinya dengan konsep maqāṣid al-syarī‘ah. Hasil kajian menunjukkan bahwa penangguhan pembagian harta bersama tidak hanya memberikan jaminan tempat tinggal yang layak bagi anak, tetapi juga mencegah potensi penelantaran anak akibat perceraian. Dengan demikian, SEMA ini mencerminkan peran negara dalam memastikan bahwa pertimbangan hukum oleh hakim harus menempatkan kepentingan terbaik anak di atas hak dan kepentingan lain yang bersifat individual, sejalan dengan tujuan syariat untuk mewujudkan jalb al-maṣāliḥ dan menolak dar’ al-mafāsid.]